Peningkatan Kinerja Pegawai Berbasis Kepemimpinan Islam Dan Insentif Dengan Komitmen Afektif Di Yayasan Al-Falah Musi Banyuasin - Arif Fadillah; Mutamimah Mutamimah (Journal of Innovative and Creativity, 2026)
This study aims to analyze the effect of Islamic Leadership and incentives on the performance of human resources (HR), both directly and indirectly through affective commitment as an intervening variable at Al-Falah Sukajaya Foundation, Musi Banyuasin. The research method used is a quantitative approach with an explanatory type of research. The population in this study were all teachers in the Al-Falah Foundation environment, with a sample of 94 respondents. Data analysis techniques using path analysis and Sobel test to test indirect effects. The results showed that Islamic Leadership and incentives significantly positively affect employee performance. In addition, affective commitment is proven to be able to mediate the relationship between Islamic Leadership and incentives to improve HR performance. These findings indicate that Islamic values-based leadership development and a fair incentive system can increase employees' emotional loyalty, which in turn has an impact on better performance. This research contributes to the management of human resources in Islamic educational institutions in an effort to improve work effectiveness and efficiency in a sustainable manner.